Pemanfaatan Limbah Kulit Buah dan Sayur Sebagai Bahan Bakar Bioetanol dengan Variasi Konsentrasi Katalis - Eva Agustina; Gita Ika Safitri; Irssa Intan Fatiha; Muhammad Iqbal Pratama; Rahmania; Ria Safitri; Funsu Andiarna; Irul Hidayati (Talenta Publisher (Universitas Sumatera Utara), 2021)
Fossil fuels are included as non-renewable energy sources, so its presence in Indonesia is decreasing. One of the renewable energy sources that can be obtained easily is bioethanol, this energy is obtained from organic materials containing cellulose fibers. Cellulose is hydrolyzed on a catalyst and fermented to obtain bioethanol. The aim of this study was to determine the effect of variations in the concentration of catalysts in the production of bioethanol from market organic waste (fruit peels and vegetables). There are three stages of converting organic waste into bioethanol, including converting green vegetables waste and fruit peels (polysaccharides / cellulose) into monosaccharides (simple sugars) through a hydrolysis process followed by a fermentation process using Saccharomyces cerevisiae and EM4, then separating ethanol and water using a distillation process. The resulting products are analyzed using a quantitative test to determine density and a qualitative test to determine color change. The results showed that the ethanol obtained from the addition of H2SO4 catalyst with concentrations of 0.5% and 1% had almost the same specifications as standard ethanol based on density calculations and color change tests. The highest ethanol yield percentage was obtained from the concentration of H2SO4 1%.